PENGARUH FAKTOR PSIKOLOGI WISATAWAN TERHADAP PENGAMBILAN KEPUTUSAN BERKUNJUNG KEMBALI PADA MASA PANDEMI COVID-19 DI DESA WISATA PUJON KIDUL - Raudya Wicaksono; Sukaatmaja I Putu Gde; Putra I Nyoman Darma (Forestry Study Program University Of Mataram, 2023)
This study was conducted with the aim of analyzing consumer decisions to visit Pujon Kidul Tourism Village, Malang Regency, East Java during the Covid-19 pandemic. There are five factors used in this study, namely motivation, perception, attitude, learning, and personality. This study uses the associative method with a quantitative approach. Data were collected using a questionnaire method with a sample of 100 visitors. To analyze the data, the researcher used Structural Equation Modeling (SEM) based on PLS (Partial Least Square). This research concludes that motivation, perception, attitude, and learning have a significant positive effect on the decision to visit Pujon Kidul Tourism Village. The higher the motivation of tourists to travel, the better the perception of tourists towards a destination, the more information and knowledge about the description of a place as a tourist destination, and the easier it is for tourists to get information about tourist destinations, the higher the decision to visit. Meanwhile, personality has no significant positive effect on visiting decisions, which means that an increase in personality factors has an impact but is not significant on visiting decisions.